MAJELIS TARJIH DAN TAJDID SEBAGAI PEMENGANG OTORITAS FATWA MUHAMMDIYAH - edis, M.hidayat; Bus, Yecky (Jurnal AL-AHKAM, 2020)
Fatwas were born as an answer to problems that arise in society. As an instrument in producing law, fatwas play an important role in public life in Indonesia. Muhammadiyah asone of the community organizations has produced fatwas to answer various problems with the ijtihad bayani, ta'lili, and istislahi methods. The resulting fatwas were published in Suara Muhammadiyah magazine, Religious Questions and Answers book and the book Himpunan Putusan Tarjih (HPT). MTT fatwas are the result of collective ijtihad carried out by MTTmanagement. However, this fatwa is not ijma 'as in the terminology of fiqh. Ulama-ulama who play a role in collective ijtihad do not cover all scholars who are a requirement for an ijma ', because the activity of ijtihad jama'i (collective ijtihad) is possible to be carried out several times by different actors at different times and places, so that the results According to thelegal findings, it is possible that there is a difference between one activity of ijtihad jama'i (collective ijtihad) and another, although on the same issues. The fatwas produced by MTT do not have formal binding strength. Every fatwa decision that has been stipulated does not have to be carried out by Muhammadiyah members because the level of strength of the fatwa is not the same as ijtihad. This research is a research library (library research) because the dataneeded for the preparation of this scientific work are contained in primary sources in the form of Tafsir al-Manar, a collection of Fatwa Muhammad Rasyîd Ridhâ and a collection of Fatwas from the Indonesian Council. In addition, the secondary sources of this study were taken from the literature related to inter-marriage. After the data was collected, the writer classified andanalyzed it by using the inductive method. The research findings are first, the cause of the difference in opinion between Muhammad Rasyîd Ridhâ and the Fatwa of the Indonesian Ulema Council is different in understanding the argument. The argument used by Muhammad Rasyîd Ridhâ is the zhahir verse of QS al-Maidah verse 5, while the Indonesian Ulama Councilbecause there is a difference in ulama, the Indonesian Ulama Council chose an opinion that is forbidden because it considers the harm to be greater than the benefits. The argument used by the Indonesian Ulema Council is mashlahah dharûriyah. Second, the opinion of Muhammad Rasyîd  Ridhâ  which  allows  marrying  non-Muslim  women  (Ahl  al-Kitâb)  by  adhering  tozahirnash in line with maqâshid al-syarî'ah, in this case there is one method of knowing the meaning shari 'namely bi zhawahiri al-nushush (text).Keywords: Nikah, Maqâshid al-Syarî'ah ', Muhammad  Rasyîd  Ridhâ,  Indonesian UlemaCouncil..